231Pa/230Th (Pa/Th) and related radioisotope concentrations from eleven Atlantic sediment cores for the Holocene - Lippold, Jörg; Scheen, Jeemijn; Pöppelmeier, Frerk; Süfke, Finn; Stocker, Thomas F; Regelous, Marcel (PANGAEA, 2024)
231Pa/230Th and related radioisotope concentrations from eleven Atlantic sediment cores for the Holocene. The concentrations of sedimentary 231Pa, 238U, 230Th, and 232Th were measured using ID-ICP-MS in a co-operation between Heidelberg University and GeoZentrum Nordbayern, FAU Erlangen‐Nürnberg.